دراسة انتشار الصداع النصفي في مدينة صبراتـه - امبية هبهب أ.سامية الثابت; محمد المحجوبيأ. فتحية العارف (Aljameai, 2022)
المستخلص: الصداع هو أكثر اضطرابات الجهاز العصبي شيوعآ، ويتسبب في حالة من عدم الارتياح وعدم التركيز، ومن أنواع الصداع الشائعة,. الصداع النصفي، الصداع الناتج عن التوتر،والصداع العنقودي ويعتبر الصداع النصفي من الاضطرابات المؤلمة واسعة الانتشار والمعقَدة وتتسبب في الألآم ومشاكل في حياة المريض وأسرته. وبالرغم من انَ أسباب الصداع النصفي غير مفهومةإلا اِنَه أكثر انتشارآ بين النساء والذي يمكن أنْ يكون بسبب التقلبات الهرمونية التي ترافق الدورة الشهرية. وفي هذه الدراسة تمَّت مقارنة الصداع النصفي لعينة الدراسة المتكونة من عدد 101 من الأشخاص منهم 79 إناث بنسبة 78.2% و22 ذكور بنسبة 21.80% , تمَّ توزيع استبيان علي جميع أفراد العينة وتجميع وتبويب البيانات. أظهرت النتائج أنَّ نسبة الإصابة بالصداع النصفي كانت أعلي في الأشخاص بين سن (17-26) سنة حيث بلغت نسبتهم في العينة 54.5% من مجموع العينة. وأظهرت الدراسة أنَّ معظم الأفراد في العينة (83.2%) لم تكن لديهم إصابات سابقة في الرأس‘ وأنَّ (79.2%) من العينة لا يعانون من أي أمراض مزمنة، كما أظهرت الدراسة أنَ مدة نوبة الصداع النصفي تستمر من ساعة إلي 4 ساعات في 36.6% من عينة الدراسة وتكررت هذه النوبات مرة واحدة أو مرتين شهريا في 49.5% من عينة الدراسة. كما أظهرت الدراسة أنَ نسبة كبيرة (70.3%) من الأشخاص في عينة الدراسة يستخدمون أدوية مسكنة للتخفيف من حدة نوبات الصداع النصفي. Abstract: Headache is the most common type of neuron system disorder and it is usually combined with pain, discomfort, and lack of focus. The most common types of headache include migraine, tension headache, and cluster headache. Migraine is considered as a very common complicated pain full and widely spreader type of headache, and it is usually a combined with pain that caused problems and discomfort for the patient and his family. Even though the real causes of migraine are not known, it is more common among women which might be due to hormonal changes during menstrual cycle. In this study, a sample of 101 people with migraine were investigated the female patients were 79 which is 78.2% of the total, and the male patients were 22 which is 21.80% of the total. A questionnaire was handed to all patients and results were then analyzed. The results showed that more than half (54.5%) of the sample of the study were between (17-26) years of age. The results also showed that most of the patients (83.2%) did not have any previous accidents on their heads, also a big percentage at them (79.2%) did not suffer from any chronic disease. The results also showed that migraine incidence period takes between one and 4 hours in 36.6% of the patient, and the incidence of migraine frequently between one and two times in 49.5% of the patient. The results also showed that a big percentage (70.3%) of this sample are using analgesic drugs to reduce the symptoms of migraine.